Carbazole-containing sulfonamides and sulfamides: Discovery of cryptochrome modulators as antidiabetic agents. Issue 3 (1st February 2016) - Humphries, Paul S.; Bersot, Ross; Kincaid, John; Mabery, Eric; McCluskie, Kerryn; Park, Timothy; Renner, Travis; Riegler, Erin; Steinfeld, Tod; Turtle, Eric D.; Wei, Zhi-Liang; Willis, Erik
Graphical abstract: Abstract: A series of novel carbazole-containing sulfonamides and sulfamides were synthesized. A structure–activity relationship study of these compounds led to the identification of potent cryptochrome modulators. Based on the results of efficacy studies in diet-induced obese (DIO) mice, and the desired pharmacokinetic parameters, compound41 was selected for further profiling.